Impact of management practices and managerial ability on the financial performance of aquaculture farms in Bangladesh. Issue 1 (2nd January 2020) - Rahman, Md Takibur; Nielsen, Rasmus; Khan, Md Akhtaruzzaman; Ankamah-Yeboah, Isaac
Abstract: Theoretical and empirical research on farm management suggests that management practices and managerial ability affect farms' financial performance. However, the explicit application of these concepts is scarce within the aquaculture field. In this study, the impact of management practices and managerial ability on the financial performance of aquaculture farms are investigated in Bangladesh. The aquaculture sector in Bangladesh mainly comprises small extensive freshwater pond farms, a good representative of aquaculture production in developing countries. The results indicate that both management practices and managerial ability affect farm financial performance. These findings emphasize that small-scale extensive aquaculture can be made more economically sustainable in developing countries if knowledge on improving management practices and managerial abilities are disseminated to farmers and policymakers.